2021
DOI: 10.3390/ijms222413352
|View full text |Cite
|
Sign up to set email alerts
|

VEGFB Promotes Myoblasts Proliferation and Differentiation through VEGFR1-PI3K/Akt Signaling Pathway

Abstract: It has been demonstrated that vascular endothelial growth factor B (VEGFB) plays a vital role in regulating vascular biological function. However, the role of VEGFB in regulating skeletal muscle cell proliferation and differentiation remains unclear. Thus, this study aimed to investigate the effects of VEGFB on C2C12 myoblast proliferation and differentiation and to explore the underlying mechanism. For proliferation, VEGFB significantly promoted the proliferation of C2C12 myoblasts with the upregulating expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Likewise, the expression of p-AKT not total AKT was increased in NAT10-OE cells while decreased in siNAT10 cells ( Figure 4A ). The increased p-AKT activates the PI3K-AKT pathway and promotes cell proliferation ( 18 20 ) by facilitating the synthesis of anti-apoptotic proteins or phosphorylating and inactivating pro-apoptotic Bcl-2-related death-initiating proteins ( 21 ). We subsequently verified that the pro-apoptotic protein BAX was decreased upon NAT10 overexpression, and vice versa ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the expression of p-AKT not total AKT was increased in NAT10-OE cells while decreased in siNAT10 cells ( Figure 4A ). The increased p-AKT activates the PI3K-AKT pathway and promotes cell proliferation ( 18 20 ) by facilitating the synthesis of anti-apoptotic proteins or phosphorylating and inactivating pro-apoptotic Bcl-2-related death-initiating proteins ( 21 ). We subsequently verified that the pro-apoptotic protein BAX was decreased upon NAT10 overexpression, and vice versa ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been revealed that VEGFB plays a vital role in regulating different kinds of cell-type proliferation and differentiation in vivo and in vitro, including cardiomyocytes and endothelial cells [ 35 , 36 ]. Our previous study also demonstrated that VEGFB promotes myoblast proliferation and differentiation via VEGFR1-PI3K/Akt signaling pathway in vitro [ 21 ]. Although the functional effects of VEGFB on the fatty acid metabolism in skeletal muscle and the heart have been well demonstrated, to the best of our knowledge, the biological role of VEGFB in skeletal muscle development in vivo is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that vascular endothelial growth factors and receptors are involved in the process of fat deposition and metabolism and skeletal muscle growth [ 18 , 19 , 20 ]. In addition, our previous study has demonstrated that vascular endothelial growth factor B (VEGFB), a vascular endothelial growth factor family member, promotes myoblast proliferation and differentiation [ 21 ]. VEGFB binds to vascular endothelial growth factor receptor 1 (VEGFR1) and neuropilin 1 (NRP1).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis for VEGFB is more circumstantial than for other targets, but derives strength through association with NRP1. VEGFB binds to NRP1 and vascular endothelial growth factor receptor 1 (VEGFR1) seemingly to activate downstream signalling pathways important for skeletal muscle growth and repair 20 . However, being a homolog of VEGFA, it is thought that VEGFB may offer similar or redundant functionality to VEGFA 20 .…”
Section: Discussionmentioning
confidence: 99%
“…VEGFB binds to NRP1 and vascular endothelial growth factor receptor 1 (VEGFR1) seemingly to activate downstream signalling pathways important for skeletal muscle growth and repair 20 . However, being a homolog of VEGFA, it is thought that VEGFB may offer similar or redundant functionality to VEGFA 20 . As such, the known SARS-CoV-2 spike protein subversion of the VEGFA/NRP1 pronociceptive signaling 8 may also apply here.…”
Section: Discussionmentioning
confidence: 99%